Increasing Awareness of Papillomaviruses and Their Association with Human Diseases - Divbandi, Marzieh; Tabarraei, Alijan; Nematollahi, Shahrzad (Archives of Men's Health, 2020)
The papillomavirus family is known to be responsible for a quarter of virus-related cancers worldwide. High-risk types are the causative agents of anogenital, cervical and various cancers of the mouth, throat, intestines, vagina, penis and anus. Cervical cancer and various other malignancies induced by papillomaviruses are a global health problem, and the growing prevalence of these diseases indicates the need to increase awareness of this viral family. In this review, published articles during 2001-2020 were searched using keywords such as Papillomavirus, Cervical Cancer and Papilloma Vaccine. Our review represents the results of the association of high-risk HPV serotypes with many malignancies in human. Furthermore, issues such as HPV vaccination, cervical cancer screening, and other preventive programs worldwide are discussed.